Visiting entertainment venues and sexual health in China. - Li, Li; Wu, Zunyou; Rotheram-Borus, Mary Jane; Guan, Jihui; Yin, Yueping; Detels, Roger; Wu, Sheng; Lee, Sung-Jae; Cao, Haijun; Lin, Chunqing; Rou, Keming; Liu, Zhendong (Archives of sexual behavior, 2009)
Entertainment venues in China are associated with risky sexual behavior. Most previous studies related to entertainment venues in China have focused on sex workers and commercial sex, but this study addressed sexual health in a sample of the general urban population. A randomly selected sample of market vendors (n = 4,510) from an eastern city was recruited and assessed to examine relationships between entertainment venue visits and sexual risk. Both behavioral (self-reports of unprotected sex) and biomedical (STD test results) measures were used. About 18% of the sample (26.8% of men and 9% of women) reported visiting entertainment venues in the past 30 days. Those who visited entertainment venues were more likely to be male, younger, single, with higher education, and to have more discretionary income. For both men and women, visiting entertainment venues was a significant predictor for unprotected sex and STD infection. Gender differences were observed in predicting unprotected sex and STD infections. Entertainment venues could be potential sites for place-based intervention programs and outreach for the general population.
Keywords: Adult; Alcohol Drinking; China; Computers; Education; Female; Health; Humans; Interviews as Topic; Logistic Models; Male; Marital Status; Questionnaires; Sex Characteristics; Sexual Behavior; Sexually Transmitted Diseases; Socioeconomic Factors